Pengaruh Pengembangan Karir Dan Motivasi Kerja Terhadap Kinerja Pegawai Di BKPSDM Kabupaten Solok Selatan - Nora Yolinza; Doni Marlius (Pusat Riset dan Inovasi Nasional, 2023)
The research was conducted at the BKPSDM office in South Solok Regency. the aim is to determine the effect of career development and work motivation on employee performance at the BKPSDM office in Solok Selatan district. This study uses quantitative methods. population are employees of the South Solok district BKPSDM office, as many as 42 respondents. the sampling technique used is the total sampling technique, so that the sample in this study were 42 respondents. data analysis using multiple linear regression analysis assisted by the computer program SPSS for windows version 16. The results of the study show that career development partially has a positive and significant impact on employee performance at BKPSDM Solok Selatan district, Work motivation simultaneously has a positive and significant effect on employee performance at BKPSDM, Solok Selatan district.